2017
DOI: 10.13005/ojc/330221
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aqueous Extract of Pseuderanthemum acuminatissimum Radlk Leaves To Mediate The Synthesis of Gold Nanoparticles and Their Anti Eschericia coli Activity

Abstract: This research provides a new route to obtain gold nanoparticles (AuNPs) using an aqueous extract of air-dried Pseuderanthemum acuminatissimum Radlk leaves. The extract was used as a reducing agent in the formation of metallic gold from gold ions, and acted as a stabilizer of the obtained AuNPs in the reaction mixture. The formation of AuNPs in aqueous extract of P. acuminatissimum Radlk leaves was validated by change in color and the appearance of surface plasmone resonance (SPR) peak at 552 nm. The average si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The filtrate was retained for further experiments. The synthesis of silver nanoparticles was carried out following our previous result in the synthesis of gold nanoparticles with slight modification [20] by direct addition of 2 mL of silver nitrate (0.01 M) to the M. malabathricum fruits extract (4 mL) in a reaction tube under constant stirring for 1 hour using a magnetic stirrer at room temperature. UV-Visible spectrophotometry (400 nm -800 nm) was used to monitor the progress of the reaction at various intervals.…”
Section: Methodsmentioning
confidence: 99%
“…The filtrate was retained for further experiments. The synthesis of silver nanoparticles was carried out following our previous result in the synthesis of gold nanoparticles with slight modification [20] by direct addition of 2 mL of silver nitrate (0.01 M) to the M. malabathricum fruits extract (4 mL) in a reaction tube under constant stirring for 1 hour using a magnetic stirrer at room temperature. UV-Visible spectrophotometry (400 nm -800 nm) was used to monitor the progress of the reaction at various intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis functional group of aunps FTIR measurements were performed to identify the biomolecule compounds in Muntingia calabura L. leaves which are responsible for the reduction, capping and stabilization of the gold nanoparticle bioreduction 14 . Fig.…”
Section: Fig 3 Uv-vis Absorption Spectra Of Gold Nanoparticles At Incubation Time (Day Variations)mentioning
confidence: 99%
“…Analysis revealed that spherical gold nanoparticles with an average diameter of 27 nm have a surface plasmon resonance peak at 539 nm. 15 The existing research has stimulated our interest in developing a green method of coating natural zeolite with metallic gold, and characterizing the resulting products. We believe our research will significantly contribute to the development of competitive green substances that are compatible with existing materials.…”
Section: Introductionmentioning
confidence: 99%